Role of oxidative stress in antituberculous drugs (individuals and combined) cytotoxicity in HepG2 cells - Elmorsy, Ekramy; Attalla, Sohayla M.; Al-Ghafari, Ayat; Nwidu, Lucky Legbosi (Malaysian Society of Applied Biology, 2016)
Hepatotoxicity is a common side and toxic effect of Antituberculous (Anti-TB) drugs with reported higher incidence with anti-TB combinations. Oxidative stress was shown to have a role. This study examined oxidative stress effects of the first line Anti-TB drugs; Rifampicin (RIF), isoniazid (INH) and pyrazinamide PZA (individually and combined) on HepG2 cells. MTT assay (3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) was used to study the cytotoxic effect of the tested Anti-TB drugs. The effect of anti-TB drugs on total glutathione HepG2 cells and the production of reactive oxygen species (ROSs) were studied (individually and in combinations). Furthermore, the protective effect of the antioxidant reduced glutathione was assayed. The data revealed that the tested anti-TB were cytotoxic to HepG2 cells. RIF was the most potent. The tested drugs in their estimated IC50s, to different extents, enhanced significantly (P<0.0001) ROSs production and decreased total glutathione (P <0.0001). Furthermore, 48 hours pre-treatment with INH (3mM) significantly increased ROS production and decreased glutathione with RIF (0.1mM) (P <0.01 and P <0.05 respectively) and PZA (10 mM) (P <0.01 and P <0.05 respectively). Combined RIF (0.1mM) and INH (3mM) significantly decreased total glutathione (P<0.05 for each) and increased ROSs production (P<0.05) in HepG2 cells (P<0.05 for each). Interestingly, reduced glutathione (GSH) significantly decreased the cytotoxicity of RIF and INH (P=0.005 and 0.015, respectively). These data showed that oxidative stress play a crucial role in anti-TB induced hepatotoxicity, which can be alleviated by inclusion of antioxidant in therapy, though there is need of clinical trials. Moreover, combined anti-TB therapy should be considered as a risk factor with any other oxidative liver injuries.